Effect of Nellore (Bos indicus) donor age on in-vitro embryo production and pregnancy rate - Silva, Marina Oliveira de; Borges, Marcelo Sant'Ana; Fernandes, Luana Gomes [UNESP]; Rodrigues, Naiara Nantes [UNESP]; Watanabe, Yeda Fumie; Joaquim, Daniel Carlino; Oliveira, Clara Slade; Feuchard, Viviane Luzia Silva da; Cyrillo, Joslaine Noely Santos Gonçalves dos; Mercadante, Maria Eugênia Zerlotti; Monteiro, Fabio Morato [UNESP] (Wiley, 2022)
The aim of this study was to evaluate the effect of age of Nellore (Bos indicus) donors on the efficiency of in vitro embryo production (IVEP) and pregnancy rate. Thirty-six donors, including 11 female calves (13 ± 0.61 months), 17 prepubertal heifers (25 ± 0.78 months) and 8 cows (83 ± 28 months), were submitted to 3 procedures of ovum pickup (OPU) on random days of the estrous cycle at intervals of 21 days. Caspase-3 and IGFBP2 were quantified in oocytes and blastocysts for the evaluation of oocyte and embryo quality. The produced embryos were vitrified (n = 445) and transferred to synchronized recipients. Cows produced a larger number of follicles (cows: 54.5 ± 6.2; calves: 20.0 ± 0.57; prepubertal heifers: 20.8 ± 0.46), total oocytes (cows: 45.97 ± 7.22; calves: 28.93 ± 6.14; prepubertal heifers: 27.21 ± 4.94) and cleaved oocytes (cows: 21.14 ± 4.22; calves: 13.09 ± 3.72; prepubertal heifers: 12.4 ± 3.19). The cleavage rate was similar between age categories; however, cows tended (p < 0.07) to produce a larger number of blastocysts (9.74 ± 2.26) per OPU than calves (5.57 ± 1.99) and prepubertal heifers tended to have a higher blastocyst yield (35.4%) than calves (27.1%) (p <.07). The expression levels of IGFBP2 and caspase-3 were higher in oocytes derived from calves compared to the other two categories. The pregnancy rate was higher in calves (43.1%) and cows (40.4%) than in prepubertal heifers (33.8%) (p =.03). Despite the larger numbers of follicles and viable oocytes in cows, the blastocyst production results and pregnancy rates obtained indicate that the use of young females as oocyte donors in IVEP is feasible and may contribute to reduce the generation interval.
Keywords: caspase-3; embryo quality; IGFBP 2; IVEP; oocyte quality